Foreign Banks and Trade : Bridging the Information Gap? - De Nicola, Francesca; Tan, Shawn W. (World Bank, Washington, DC, 2017)
Foreign banks can play an important role in facilitating international trade. Most research has focused on the financing role banks can play, but less is known about the information role. This paper estimates a gravity model using sub-regional data from Turkey between 2002 and 2010 to explore whether foreign banks promote trade through the information channel. The presence of a foreign banks from a trade partner promote the exports of the sub-region. In addition, the analysis finds that the footprint of these foreign banks matters more for exports than the presence of these banks and the level of financial development of the sub-region. Banks from countries neighboring trade partners can also decrease exports. When taking into account financial conditions and examining the differential impacts during the recent financial crisis, the analysis finds that the footprint of foreign banks has the largest impact on trade.